2017
DOI: 10.1007/s41104-017-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

A holistic investigation of natural gas–diesel dual fuel combustion with dual direct injection for passenger car applications

Abstract: This publication covers the investigation of a dual fuel combustion process for passenger car applications using natural gas and diesel as fuels. In the literature a widely studied dual fuel concept is the combination of port fuel injection of natural gas and direct injection of diesel. The challenge of this concept is a high emission of unburned hydrocarbons at low load operation as previous publications show. The proposed concept features a low pressure direct injection of natural gas in combination with dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another possibility for direct injection is low-pressure direct injection of around 16 bar. Fasching et al [168] performed a detailed analysis of this concept and reported that further studies must be performed in order to reduce engine-out and tailpipe methane emissions.…”
Section: Power Train Technology and Vehicle Availabilitymentioning
confidence: 99%
“…Another possibility for direct injection is low-pressure direct injection of around 16 bar. Fasching et al [168] performed a detailed analysis of this concept and reported that further studies must be performed in order to reduce engine-out and tailpipe methane emissions.…”
Section: Power Train Technology and Vehicle Availabilitymentioning
confidence: 99%
“…The mass flow rate of injected NG is simulated as a chocked flow through a singlehole injector. The chocking condition is practically chosen for NG injection since it ensures stable injection [15]. The injection pressure of NG is chosen to be equal 10 bar since this value can maintain a critical pressure ratio through the injector nozzle for the selected injection timing, which is equal to IVC, and engine loads.…”
Section: Fuels Injection Modelsmentioning
confidence: 99%
“…The benefits include improvements in thermal efficiency through increasing the flame speed of NG resulting from the combustion of locally stoichiometric NG-air mixture [13]. However, the main drawbacks of this method include the increased complexity of the injection system due to the high injection pressure and the increase in soot emissions due to the presence of rich mixture zones [14,15]. Engine simulations are valuable tools for evaluating the performance and emission parameters.…”
Section: Introductionmentioning
confidence: 99%